Supporting developing countries in WTO dispute settlement - Louise Johannesson (Research Institute of Industrial Economics (IFN), 2016)
Even though the World Trade Organization (WTO) ensures equal access to the dispute settlement system, the legal process is still highly costly, an aspect that primarily affects poorer developing countries. It is feared that this imbalance discourages developing countries from filing and defending complaints against richer countries. In an effort to reduce these costs and increase participation by developing countries, the WTO provides two supporting measures: legal assistance, and preferential panel composition. The latter reserve one slot on the panel exclusively for a judge from a developing country. This paper examines whether these measure leads to increased participation, applying a model that takes into account the decision to participate by both the developing and the industrialised country. We show that both measures encourage developing countries to file more complaints, yet, the number of adjudicated disputes may not increase accordingly. Furthermore, the measures may decrease developing countries' average success rate in panel. Using unique data, we also empirically inspect the presumed benefit of including a developing-country judge on the panel (Art. 8.10) and find a negative impact on the developing-country success rate. This apparent inconsistency is, however, resolved within the theoretical framework through a selction mechanism. The model developed in this paper aims to provide a more systematic approach to policy evaluation of certain types of supporting measures in the WTO.
Keywords: F13; K41; 330; WTO dispute settlement; Developing countries; Special and Differential Treatment provisions; Legal capacity; Panelists